Establishing Chickasaw plum for wildlife in northwestern Oklahoma - Adam West; Rodney E. Will; Edward Lorenzi; Fred S. Guthery (Wildlife Society Bulletin)
Abstract Chickasaw plum (Prunus angustifolia) provides cover (escape, thermal, nesting, resting) and food (foliage and fruit) for wildlife in the southern Great Plains. Establishing plum may increase abundance of some wildlife species and species diversity on areas deficient in woody cover. To provide recommendations for establishment methods of Chickasaw plum, we tested effects of tillage, planting date, and competition control on survival and growth of bare‐root seedlings (BRS), coppiced transplants (CT), and intact transplants (IT) of Chickasaw plum planted on sandy sites in Woods County, Oklahoma, USA, during 2007–2011. Tillage did not affect survival or growth. After 4 years, BRS had higher survival than CT or IT (83%, 26%, and 18%, respectively). Bare‐root seedlings also outperformed transplants in height and diameter development and coppicing transplants did not have a long‐term negative effect. At the end of 4 years, heights were 70 cm, 55 cm, and 52 cm, while ground line diameters were 14 mm, 9 mm, and 9 mm, for the BRS, IT, and CT propagules, respectively. Based on crown spread and an initial planting density of 60 × 60 cm, stands should be fully established by age 6. Planting in mid‐spring increased survival of CT by >33% compared to late‐winter or early spring planting. Competition control using weed‐barrier cloth increased plum survival by 13%. Overall, BRS performed well, but if seedlings are not available, local transplants can be taken and planted at higher densities to achieve similar results. If using local transplants, we recommend coppicing to increase survival and hasten establishment. © 2012 The Wildlife Society.